Comentario sobre el indicador de ahorro genuino propuesto por el Banco Mundial - Falconí, Fander (2001)
The World Bank presents so-called "gonuine savings" data for certain countrics including Locuador. This article makes an argument against the World Bank's figures because In obtaining the genuine savings indicator, one must define and measure the reduction of "natural capital” in monetary terms as well as some negative externalities such as carhon dioxide emissions. Similarly: the World Banks genuine savings jenore the eftects of international commerce, which means that gcnuine savings cannot be used as a measure of sustainability on a global level and present serious problems on a local level. The article will discuss the case of Ecuador and will show that if one incorporates data mcasuring of the destruction ¡and exhaustion of certain natural resources and the minimum negative externalities of petroleum extraction, the reduction of "natural capital" would be greater and the figures for genuine savings should be modihied.